Are jail sanctions more punitive than community-based punishments? an examination into the perceived severity of alternative sanctions in community supervision - Wodahl, Eric J. (Criminal justice policy review, 2020)
The use of sanctions in community supervision has received considerable attention in recent years. Fueled in large part by the attention given to the swift, certain, and fair (SCF) sanctioning model, many agencies have adopted sanctioning programs, which often rely heavily on the use of short-term jail incarceration. In addition to jail, there exist a number of alternative, community-based punishments that can be utilized to respond to instances of noncompliance, including enhanced drug testing and community service hours. Little is known, however, about how individuals perceive community-based sanctions compared with jail. This study addresses this issue by examining perceptions of sanctions among individuals under community supervision. Survey findings indicate that community-based punishments are not viewed as being substantially less punitive than jail incarceration. In addition, perceptions of sanction severity are influenced by a variety of individual, experiential, and supervision-level factors. The policy implications of the study findings are discussed.